The (de)professionalisation of the gay male academic identity: Locking the closet door on South African university campuses. Issue 4 (1st October 2016) - Rothmann, Jacques
ABSTRACT: Considered as a principal method in organising forms of sexual orientation, the heterosexual/homosexual binary emphasises the centrality of heteronormativity in the everyday lives of social and sexual actors; thus, homosexuality is not only differentiated from heterosexuality, but potentially also rendered subordinate to its heterosexual counterpart. Using this as a point of departure, this article focuses on a critical qualitative sociological study undertaken into the influence of a binary logic on gay male academics on South African university campuses. The primary emphasis was on these men's choice either to professionalise or deprofessionalise their gay male identity on their respective university campuses through engaging the contemporary research on the experiences of self-identified homosexual academics as well as the seminal contributions of Erving Goffman (1971) and George Herbert Mead (1962). It was evident from the findings that the participants conform to heteronormativity on their respective university campuses through consciously reflecting on the expectations of their generalised other.